The effects of microparticulate diets containing different lipid sources on the growth and survival of rabbitfish (Siganus Guttatus, Bloch) larvae - Gomes, Luiz Antonio de Oliveira (College of Fisheries, University of the Philippines in the Visayas, 1988)
Three microparticulate diets (MPD) containing different lipid sources each, soybean oil, cod liver oil and pork lard, and a control diet, Artemianauplii, were fed to rabbitfish larvae. The experiment was conducted with larvae from 25 to 50 days after hatching under 225 liter tanks with a flow-through water system. Results showed that rabbitfish larvae can readily accept and can be reared solely with MPD, at least starting day 25. Survival rates from 78.6% to 83.8% were obtained among all treatments fed MPD.Rabbitfish larvae had remarkable ability to utilize different sources of lipids from the diets. All the MPD had normal effects on the growth, external body appearance and the metamorphosis of the larvae.